Kesesuaian Kurikulum Program Studi Pendidikan Teknik Bangunan Universitas Negeri Jakarta Dilihat dari Kompetensi Kerja Berdasarkan Standar Kompetensi Kerja Nasional Indonesia (SKKNI) Sektor Jasa Konstruksi - Dyone Septianis Herlambang; R Eka Murtinugraha; Gina Bachtiar (LPPM Universitas Negeri Jakarta, 2013)
The Objectives of this study to determine the suitability of the curriculumpercentage Building Technical Education Program Studies, State University ofJakarta seen from the competence requirements of construction work in theworld of work. Where the research conducted in the Department of CivilEngineering, State University of Jakarta. The method used is the method ofobservation.The data used in this study is SKKNI of position Young ExpertsImplementing Structure, Young Experts Construction Management, SkilledConstruction Supervisors, and young Experts Quantity Surveyor. Data used forthe course syllabus related to the job, the Construction Management, Scienceof Building Materials, Health and Safety, Practice of Soil Mechanics, BudgetPlan, Environmental Impact Assessment, and Practice Test Materials. Dataprocessing is done by creating a checklist tables and calculation of thepercentage.Results of this study are subject Construction Management 50%according, Science of Buiding Materials 92,85% according, Health and Safety28,57% according, Practice of Soil Mechanics 92,85% according, Budget Plan85,71% according, Environmental Impact Assessment 14,28% according, andPractice Test Materials 85,71% according. There is congruence between theEducation Program Building Engineering curriculum, State University of Jakartawith SKKNI. Of 7 subjects who reviewed syllabus, 4 course syllabus is inaccordance with SKKNI, 2 course syllabus is quite in accordance with SKKNI,and 1 course syllabus is not in accordance with SKKNI